O Trabalho Colaborativo entre o professor de Educação Especial que atua na Sala de Recursos Multifuncionais e o do ensino comum em escolas públicas - Teixeira, Andrise (2021)
This study aimed to investigate the Collaborative Work between the Special Education teacher, who acts in Multifunctional Resources Classrooms, and the teacher of the regular education. This factor is considered fundamental to the process of schooling and learning of students with special educational needs, as well as their unfolding in the teaching-learning process, that means, in the pedagogical praxis. The qualitative research of exploratory character was opted, through semi-structured interviews, with audio recording of the contents. The city of Cascavel was divided in five regions, North, South, East, West and Central, and in each of them two schools were selected, the ones with the highest and lowest Basic Education Development Index in each area. Thirty-two teachers took part in the research, considering that eleven of them act in Multifunctional Resources Classrooms, teaching Portuguese Language (10) and Mathematics (11), in 6th and 7th grade classes in the Elementary School, with students who are attended in Multifunctional Resources Classrooms. The reflection on the theoretical production presented in the Knowledge State allowed the settlement of four categories for the analysis of the data collected: professorial concept related to the Collaborative Work; articulation between Special Education teachers and regular education teachers; the pedagogical praxis and learning; and contributions, limits and challenges in the Collaborative Work. It was verified that 72% of the participants of the study was unaware of the concept of Collaborative Work, which interferes directly in the possibilities of its occurrence in the school context. Data also revealed that, while the Collaborative Work takes place in schools (69%), it happens scarcely, and restricted to informal and punctual situations, defined by the absence of systematization. According to 85% of the participants, the absence of Collaborative Work between Special Education teachers, who act in Multifunctional Resources Classrooms, and the teachers that act in the regular educational system who teach Portuguese and Mathematics, interferes negatively in the schooling process and psycho-intellectual development of students with special educational needs. Teachers (53%) pointed out that the work with these students, as in the regular education as in Multifunctional Resources Classrooms, must take into consideration methodological strategies that help achieve the individual necessities of each student, providing learning and human development. This study also revealed that the Special Education Attendance Plan, result of the joint elaboration between teachers from special and regular education, is indispensable for the schooling process of students with special needs. The work in opposite shifts was pointed out by 48% of the teachers as being the greatest obstacle related to the materialization of the Collaborative Work. The way the Collaborative Work has been performed has not promoted the necessary humanization process regarding students with special needs. The results show the urgency of public investment in initial or ongoing teachers formation/qualification, as well as actions that aim the overcoming of the marketing and excluding model arising from the capitalist production mode, which fragments the educational work and makes it, in many steps of the process, alienated. The importance of the resizing of public policies that support the Collaborative Work is highlighted in this research, not only in the aspect related to structural conditions, as equipment and pedagogical material, but also, and more relevantly, the ones that provide better working conditions to the teachers, enabling a true Collaborative Work that promotes learning and development for the students, rom the Special Education or not.